Attitudes, Awareness, and Willingness of Iranians Toward Using Telemedicine in Post‐COVID Era: A Cross‐Sectional Study - Marsa Gholamzadeh; Hamidreza Abtahi; Reza Safdari; Elham Haghshenas; Mehrnaz Asadi Gharabaghi; Besharat Rahimi (Health Science Reports)
ABSTRACT Background and Aims With the increased use of telemedicine during the pandemic, understanding patients' attitudes and readiness to adopt telemedicine is crucial. This study investigates the attitudes, willingness, and usage behaviors of Iranian patients toward telemedicine. Methods This cross‐sectional study took place in Iran from October 2021 to January 2023. Participants received a web‐based questionnaire consisting of five sections. The study aimed to assess Iranians' attitudes toward telemedicine following the COVID‐19 pandemic and their readiness to utilize telemedicine services in the post‐pandemic period by analyzing the gathered data. Results A total of 569 Iranian patients participated in the questionnaire, resulting in a 95% response rate. While 80% of respondents were familiar with telemedicine terms, only 30% had utilized telemedicine services before the COVID‐19 outbreak. Overall, Iranians displayed positive attitudes toward telemedicine, with over two‐thirds expressing a strong willingness to continue using telemedicine post‐pandemic. The analysis revealed a positive correlation between higher e‐health literacy scores and favorable attitudes toward telemedicine. Additionally, a significant relationship was observed between having a positive attitude toward telemedicine and prior usage of telemedicine services before the pandemic. Conclusion The findings indicated a positive attitude toward telemedicine among public patients. The results highlight a willingness to utilize remote medical services if the required infrastructure is in place to address trust issues among patients. These outcomes can be utilized to assess the feasibility of implementing telemedicine services in Iran.